Sharia Technopreneurship: MSME Growth And Gen Z Income In Palembang's Digital Era - Chici Rima Putri Pratama; Nor Balkish Zakaria; Heri Junaidi; Oki Sania Riski; Anggun Widya Pratiwi; Ananda Putra Astaman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the impact of the Sharia Technopreneurship Revolution on MSME (Micro, Small, and Medium Enterprises) growth and income generation among Generation Z in the digital era in Palembang. In the face of rapid technological advancement, Sharia technopreneurship is emerging as a crucial business model that integrates technological innovation with Sharia compliance, thereby fostering sustainable economic growth. Generation Z, characterized by their digital proficiency, plays a vital role in leveraging technology to create new economic opportunities while adhering to Islamic business ethics. A mixed-method research approach is employed, combining quantitative surveys and qualitative interviews. The sample consists of 75 MSME owners and operators selected using the Slovin formula, ensuring representative data collection. Quantitative analysis utilizes multiple regression to assess the impact of technopreneurship on MSME growth and income, while qualitative insights provide a deeper understanding of business adaptation to digitalization. Findings indicate that MSME entrepreneurs in Palembang apply Sharia principles, leading to increased consumer trust and business sustainability. Moreover, the adoption of digital platforms significantly enhances their revenue streams. This study contributes to academic discourse on Islamic entrepreneurship and offers policy recommendations for MSME development.